Factors Influencing Tax Avoidance in Food and Beverage Subsector Companies - Herman, Herman; Finesa, Firdaus Cahya (Politeknik Baubau, 2025)
This study aims to examine the extent to which liquidity, leverage, profitability, and sales growth influence tax avoidance practices. The research sample consists of 12 manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, selected using purposive sampling. Data analysis was conducted through classical assumption tests and multiple linear regression, with the support of SPSS version 25. The results reveal that, partially, liquidity proxied by the Current Ratio (CR), leverage measured by the Debt to Equity Ratio (DER), and profitability proxied by Return on Assets (ROA) each have a positive and significant effect on tax avoidance. Likewise, sales growth is shown to contribute positively and significantly to tax avoidance practices. Furthermore, when tested simultaneously, all four variables—CR, DER, ROA, and sales growth—also exhibit a significant influence on tax avoidance. These findings imply that higher liquidity, debt-based capital structure, profitability, and revenue growth can encourage firms to optimize their tax burden. Therefore, the study highlights the importance for management to design more effective financial strategies and tax policies in order to balance fiscal compliance with corporate performance.